Interorganizational Favour Exchange and the Relationship Between Doing Well and Doing Good - Nguyen, Adam; Cragg, Wesley (2012)
This article examines whether ethical business practice enhances financial performance with respect to interorganizational favour exchange. We argue that the link between the ethicality and economic utility of interorganizational favour exchange is governed by: (1) organizational–individual interest alignment/conflict and (2) the fairness or justifiability of favour exchanges from the perspective of third parties. We classify interorganizational (IO) favour exchange into four types (Business–Personal, Personal–Business, Personal–Personal and Business–Business favour exchange). Our analysis shows that the first three types of favour exchange are unethical as they involve conflicts between organizational and individual interests in one or both participating organizations that negatively affect organizational value creation. The last type of favour exchange involves organizational–individual interest alignment in both participating organizations and positively affects the capacity of those involved in the exchange to create value. Favour exchanges of this fourth variety are ethically justifiable unless they unfairly damage the legitimate interests of third parties. In the latter case, these favour exchanges create the risk of negative third party reactions, which in turn affect the sustainability of the benefits of the favour exchanges to the focal group (the dyad). Our research results advance understanding of the ethical and economic implications of IO favour exchange, counter the prejudice against this behaviour in organizations, provide ethical guidance for management and business practice, and have implications for the relationship between doing well and doing good.
Keywords: Value creation; Stakeholder Analysis; Bribery; codes of ethics; Interorganizational relationship; conflict of interest; Favour exchange; Ethical Business